RESPONS PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell.Arg) KLON PB 260 SATU PAYUNG TERHADAP PEMBERIAN PUPUK KOMPOS BATANG PISANG - Resa Keke Widiyanti; Anis Tatik Maryani; Zul Fahri Gani (Jurnal Agroteknologi, 2022)
The use of polybags and topsoil planting media often causes the development of seedlings is not maximal because the topsoil is too dense. As well as continuous inorganic fertilization is not balanced with the provision of organic fertilizers cause the planting media to become dense. One of the efforts in overcoming this is by providing compost. Compost can improve soil fertility and can improve soil structure. This research was conducted with the aim to find out how the influence of banana stem compost fertilizer on the growth of rubber seedlings (Hevea brasiliensis Muell.Arg.) Clone PB 260 one umbrella. The design used in this research is Randomized Block Design (RAK) with one factor, namely banana stem compost with 5 levels that is without composting banana stems (k0), 250 g / polybag (k1), 500 g / polybag (k2), 750 g / polybag (k3) and 1000 g / polybag (k4) with 5 group. The observed variables are the increase in the length of grafting buds (cm), the increase in the number of leaf strands (strands), the increase in the diameter of the graft buds (mm), the time of the appearance of the second umbrella bud (day), the dry weight of the header (g) and the dry weight of the roots (g) of rubber seedlings. The results showed that the influence of the treatment of banana stem compost fertilizer does not differ noticeable to the growth of rubber seedling clones PB 260 one umbrella on all parameters observations.